Risk factors of under-fives stunting in low-income households - Hilda Zakiyya Zamzamy; Suminah Suminah; Sumardiyono Sumardiyono (AcTion: Aceh Nutrition Journal, 2024)
Stunting prevalence in Indonesia is still high and far from the National medium term development plan 2020-2024 target. As many as 41% of stunted under-fives come from poor households in the stunting focus area of the Bantul Regency. This study assessed the risk factors for stunting in low-income households. This study was conducted in July 2023 in Bantul Regency using an unmatched case-control approach. Using a purposive sampling technique, 156 children under five (78 cases and 78 controls), aged 6-59 months, from low-income families registered in the village and receiving social assistance from the Ministry of Social Affairs, were chosen. Interviews were conducted to gather research data, and a validity- and reliability-tested questionnaire was used. Data were analyzed using descriptive statistics, chi-squared tests, and binary logistic regression. The findings demonstrated a substantial correlation (p<0,05) between low birth weight and antenatal care (ANC) visits and stunting; however, there was no correlation (p>0,05) between mothers’ education level, mother’s age, and children’s breastfeeding status. In conclusion, low birth weight and ANC visits are risk factors for stunting among underfives. Low birth weight is the primary cause of stunting in children under five in low-income families.